ANALISIS KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PERTUMBUHAN PENDAPATAN ASLI DAERAH (PAD) DI PEMERITAH DAERAH KABUPATEN BOGOR - Anggari, Azwina Putri; Hambani, Susy; Melani, Maria Magdalena (Komunitas Manajemen Kompetitif, 2024)
Local Own-Source Revenue (PAD) is expected to drive the economy and regional development, ultimately increasing the general income of the community. Local tax and retribution receipts should have significant potential for increasing PAD. This study aims to analyze the contribution and growth of local taxes and retributions to PAD, and categorize these components into quadrants I-IV in Bogor Regency based on the Klassen Typology. The method used in this study is descriptive with a quantitative approach. The analysis tool used in this study is the Klassen Typology analysis. The analysis results show that the growth of local taxes and retributions to PAD exhibits a fluctuating growth rate each year. The most contributing local tax is the BPHTB tax with an average percentage of 28.03%, and the highest contributing local retribution is the building permit retribution with an average percentage of 2.29%. Furthermore, based on the Klassen Typology, there are 11 components of local taxes and 10 components of local retributions that fall into quadrant I (Prime), 4 components of local taxes and 5 components of local retributions that fall into quadrant II (Potential), 1 component of local taxes and 2 components of local retributions that fall into quadrant III (Developing), and 1 component of local taxes and retributions that fall into quadrant IV (Lagging).